Enterotoxigenic staphylococcus aureus and bovine mastitis: A public health problem - de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2010)
Mastitis is an infectious disease that is highly prevalent in dairy herds and responsible for financial losses worldwide. Most losses are attributed to subclinical mastitis, which is only detectable with indirect diagnostic tests using milk samples. Staphylococcus aureus is the main causative agent of mastitis in dairy herds. The udder of infected cows is the main reservoir of S. aureus, which can be transmitted to other cows in the herd. There are numerous sources of S. aureus, including stables and feeds, equipment and animal skin of cattle and other species, as well as humans themselves. Teat skin has been implicated as an important reservoir for intramammary infection; however, transmission from man has been proposed. Various virulence factors are responsible for the symptoms and severity of infections caused by S. aureus. These factors include hemolysins, leukocidins and a group of toxic pyrogenic superantigens consisting of the toxic shock syndrome toxin 1 (TSST-1) and staphylococcal enterotoxins, which cause staphylococcal food intoxication. S. aureus enterotoxins are the most frequent cause of food intoxication, with reports of cases due to food manipulation after heat treatment. Heat destroys the vegetative bacterial microbiota in food, and non-competitive staphylococci, introduced by inadequate manipulation, may grow. Food intoxication is the result of the ingestion of foods contaminated with enterotoxigenic S. aureus during or after processing, inappropriate management or even inadequate refrigeration, enabling the growth of microorganisms and the production and release of toxins into the food which, when ingested, will produce all characteristic signs and symptoms. Staphylococcal enterotoxins are primarily found in foods that contain proteins and carbohydrates, such as dairy products, pastries, processed meat, mayonnaise, and salads. Inadequate manipulation of the product may increase the population of staphylococci until the time of pasteurization, implying the possibility of production of enterotoxins that are stable at high temperatures. Thus, pasteurized milk would be free of microorganisms, but not of enterotoxins. This milk may subsequently be offered to children who depend on it for their growth, a fact representing a serious public health problem. The objective of this chapter is to provide data for a better understanding of the pathogenesis and microbial properties that contribute to the persistence of S. aureus in dairy cattle herds.